Implementation of a Rule-Based Expert System in the Web-Based SMK Boarding and Semi Boarding Admission System by the Central Java Government - Muhammad Syaeful Fajar; Ardian Prima Atmaja; Nisa'ul Hafidhoh; MH. Ramdhani Ismar; Maulana Nur Ivansyah (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
The student admission process for boarding and semi-boarding vocational schools involves complex administrative, academic, and socio-economic criteria, which often lead to inefficiencies and inconsistencies when handled manually. This study proposes a web-based student admission system integrating a rule-based expert system to automate multi-stage selection processes in vocational high schools managed by the Central Java Provincial Government. The system was developed using a Research and Development approach with the Agile Scrum methodology. Knowledge representation is implemented through IF–THEN rules derived from officially verified admission guidelines, enabling automated scoring, ranking, and admission decisions. The proposed system was applied across three boarding schools and fifteen semi-boarding schools during the 2024 admission period. The results indicate that the system reduces processing time, improves scoring consistency, and enhances transparency and accountability in decision-making. This study demonstrates that integrating a rule-based expert system with official admission regulations provides an effective and scalable solution for large-scale student selection processes.